Characterization of clinical features of monosensitized and polysensitized allergic rhinitis patients with pollen allergy - Soyyiğit, Şadan; Öksüzer Çimşir, Dilek (The European Research Journal, 2023)
Objectives: The present study evaluates the prevalence of monosensitization and polysensitization in patients with pollen-hypersensitive moderate-to-severe persistent allergic rhinitis (AR), and determines the clinical characteristics of the two phenotypes. Methods: This retrospective cohort study included 160 patients with moderate-to-severe persistent AR among the 3,699 patients who presented to allergy outpatient clinics who were found to have hypersensitivity to pollen based on a skin prick test and/or allergen-specific IgE positivity. The patients were divided into two groups: monosensitized (hypersensitivity to pollen alone), and polysensitized (hypersensitivity to pollen and other allergens). Both groups were evaluated for allergen hypersensitivity, symptoms of AR, symptom frequency and comorbidities related to AR. Results: Of the 160 patients, 83 (51.9%) were monosensitized and 77 (48.1%) were polysensitized. The mean age was 29.5 ± 10.7 yeasrs and 28.3 ± 8.3 years, respectively and the female-to-male ratio was 42/41 and 47/30 in the two groups. Nasal congestion was remarkably more common in the polysensitized patients than in the monosensitized patients (p = 0.01). Hypersensitivity to weed mix and Cupressus arizonica pollen identified with a skin prick test was significantly more common in the polysensitized patients than in the monosensitized patients (p = 0.03 and p = 0.01, respectively). The two groups were similar in terms of the prevalence of asthma and other comorbidities related to rhinitis (p = 0.78). Conclusions: In this single-center study, the rates of monosensitization and polysensitization were found to be similar in patients with pollen-hypersensitive moderate-to-severe AR, and the clinical characteristics of the polysensitized phenotype were different from those of the monosensitized phenotype.